Radiation dose management systems—requirements and recommendations for users from the ESR EuroSafe Imaging initiative - Loose, Reinhard; Vano, Eliseo; Mildenberger, Peter; Tsapaki, Virginia; Caramella, Davide; Sjöberg, Johan; Paulo, Graciano; Torresin, Alberto; Schindera, Sebastian; Frija, Guy; Damilakis, John (European Radiology, 2020)
Abstract: The European Directive 2013/59/Euratom requires member states of the European Union to ensure justification and optimisation of radiological procedures and store information on patient exposure for analysis and quality assurance. The EuroSafe Imaging campaign of the European Society of Radiology created a working group (WG) on “Dose Management” with the aim to provide European recommendations on the implementation of dose management systems (DMS) in clinical practice. The WG follows Action 4: “Promote dose management systems to establish local, national, and European diagnostic reference levels (DRL)” of the EuroSafe Imaging Call for Action 2018. DMS are designed for medical practitioners, radiographers, medical physics experts (MPE) and other health professionals involved in imaging to support their tasks and duties of radiation protection in accordance with local and national requirements. The WG analysed requirements and critical points when installing a DMS and classified the individual functions at different performance levels. Key Points: • DMS are very helpful software tools for monitoring patient exposure, optimisation, compliance with DRLs and quality assurance. • DMS can help to fulfil dosimetric aspects of the European Directive 2013/59/Euratom. • The EuroSafe WG analyses DMS requirements and gives recommendations for users.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Dose management systems; Optimisation; Quality assurance; Radiation protection